2021
DOI: 10.1177/09645284211056941
|View full text |Cite
|
Sign up to set email alerts
|

Dry needling increases antioxidant activity and grip force in a rat model of muscle pain

Abstract: Background: Muscle pain syndromes (MPS) are one of the main causes of functional, structural and metabolic problems, being associated with tissue oxidative damage. Although dry needling is widely used in the treatment of MPS, there is little scientific evidence of its efficacy and underlying mechanisms of action. Objectives: To investigate the effects of different dry needling techniques on thermal and mechanical hyperalgesia, locomotor and functional activity, and oxidative stress markers in a rat model of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Nevertheless, research indicates that acupuncture can suppress pain transmission by reducing substance P (SP) levels and enhancing the release of endogenous opioids (8,9). A recent study revealed that acupuncture enhances strength, function, and locomotor activity in a rat model of muscle pain syndrome through its antioxidant effects (10). Additionally, another study demonstrated that acupuncture at trigger points modulated gene expression in muscle tissue, consequently promoting muscle regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, research indicates that acupuncture can suppress pain transmission by reducing substance P (SP) levels and enhancing the release of endogenous opioids (8,9). A recent study revealed that acupuncture enhances strength, function, and locomotor activity in a rat model of muscle pain syndrome through its antioxidant effects (10). Additionally, another study demonstrated that acupuncture at trigger points modulated gene expression in muscle tissue, consequently promoting muscle regeneration.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 22 A recent research suggested that dry needling improved strength, functionality and locomotor activity in a rat model of muscle pain syndromes by inducing an antioxidant effect. 23 Another research showed that the needling on trigger point changed the gene expression of muscle tissue to accelerate the muscular regeneration. 24 As for the central aspect, some scholars supported that acupuncture could activate the supraspinal and higher centres involved in pain processing.…”
Section: Introductionmentioning
confidence: 99%